Management of lingual nerve injury: a case report - P. Tiriduzzi; L. Gentili; C. Vianale; M. Coloccini; M. Messi (Publymed, 2021)
One of the most common complication associated with oral surgical procedures are iatrogenic injuries to lingual branch of trigeminal nerve. Lingual nerve damage may result in permanent lingual sensory deficit leading to symptoms, including lost or altered sensation and the development of unpleasant neuropathic pain, with consequent impaired quality of life. The surgical removal of mandibular third molars is one of the most common oral surgical procedures and it is associated with a number of perioperative complications, including nerve injuries. This paper show how to manage lingual nerve injuries.